1993
DOI: 10.1002/1097-4679(199307)49:4<586::aid-jclp2270490417>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

issues and concerns in Master's-level training and employment

Abstract: The controversy that surrounds Master's‐level training in psychology prompted a study of the training and professional activities of those with subdoctoral training. Individuals with a Master's degree in psychology and agencies that employ them were surveyed independently to ascertain the duties performed by and assigned to them. Response rates of 21% and 24% for individuals and agencies, respectively, resulted from the mailing. The results suggested a discrepancy between the projections of agencies and indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Clinical mental health counselors performed as well as clinical psychologists across both tasks and both cases, although counselors found the tasks slightly more difficult than did psychologists. Previous studies concluded that master's-level practitioners spend the majority of their professional time in direct service delivery (Robiner, Arbisi, & Edwall, 1994;Trent, 1993;Watkins, Campbell, & McGregor, 1989) and thus could be expected to have competency in the case management skills assessed in this study. For common outpatient disorders, then, client assessment and treatment planning seems well within the scope of master'slevel clinicians.…”
Section: Implications For Training and Practicementioning
confidence: 88%
“…Clinical mental health counselors performed as well as clinical psychologists across both tasks and both cases, although counselors found the tasks slightly more difficult than did psychologists. Previous studies concluded that master's-level practitioners spend the majority of their professional time in direct service delivery (Robiner, Arbisi, & Edwall, 1994;Trent, 1993;Watkins, Campbell, & McGregor, 1989) and thus could be expected to have competency in the case management skills assessed in this study. For common outpatient disorders, then, client assessment and treatment planning seems well within the scope of master'slevel clinicians.…”
Section: Implications For Training and Practicementioning
confidence: 88%
“…Master's-level providers, in the private sector, were then left to seek the credential of a psychological examiner and/or associate. Although these individuals were functioning within the range of APA's earlier stated expectations (see APA Committee on Subdoctoral Education, 1955), there was a growing dissatisfaction with the limitations of that particular license (Trent, 1993). Many master's-level practitioners felt indentured to their supervising psychologists, who were enjoying handsome incomes from the services provided by the supervisee.…”
Section: Social and Political Factorsmentioning
confidence: 98%
“…(e.g., Trent, 1993), an issue that will likely become more heated with the advent of managed care. Issues about the marketability of master's level community psychologists in comparison with other master's level individuals (e.g., MSWs, MFT, Master's in Counseling) have also been raised (Hoffnung, Morris & Jex, 1986).…”
Section: Education In Community Psychologymentioning
confidence: 99%